Analisis Kinerja Keuangan PT Bank Tabungan Negara (Persero) Tbk dan PT Bank Danamon Indonesia Tbk Periode 2020-2024 - Dian Jaatsyiah Noer’s; Uhud Darmawan Natsir; Anwar Anwar; Amiruddin Tawe; Nurman Nurman (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze and compare the financial performance of PT Bank Tabungan Negara (Persero) Tbk. (BTN) and PT Bank Danamon Indonesia Tbk. (Danamon) during the 2020–2024 period using the CAMEL method, which evaluates five key aspects of bank soundness: Capital (CAR), Asset Quality (KAP), Management (NPM), Earning (ROA and BOPO), and Liquidity (LDR). The research adopts a quantitative descriptive comparative approach, with BTN and Danamon as the research population. Secondary data were obtained from the annual financial reports of both banks published on the official Indonesia Stock Exchange (IDX) website for the 2020–2024 period. Data analysis involved calculating CAMEL ratios based on the Bank Indonesia assessment guidelines, along with hypothesis testing using the Independent Sample T-test and the non-parametric Mann-Whitney test through SPSS version 25 to determine whether significant statistical differences existed between the two banks. The findings reveal that the financial performance of BTN and Danamon consistently fell within the “Fairly Healthy” category throughout the observed period. Specifically, BTN demonstrated stronger performance in terms of capital adequacy (CAR), while Danamon showed better results in asset quality (KAP) and profitability (ROA). However, the overall results of the Mann-Whitney test yielded a significance value of 0.465, which is greater than the alpha level of 0.05. This indicates that there is no statistically significant difference between the overall financial performance of BTN and Danamon as measured by the CAMEL method. These results suggest that although the two banks exhibit strengths in different aspects, their overall financial health remains relatively comparable.